Utilization of Technology in Facilitating Customer Purchases and Payments at Charles & Keith - Puspito, Galuh Retno; Oktafia, Renny (PT Inovasi Pratama Internasional, 2024)
With its continued development, technology is now not only used as a communication medium, but can be used as a means of payment or online shopping. Currently, the public or customers are offered many digital shopping and payment methods. PT Kurnia Ciptamoda Gemilang under the Charles & Keith brand has utilized existing technological advances by implementing an online shopping model via website and chat shop as well as a payment method using e-money, without eliminating the cash payment method. Despite innovation, many Charles & Keith customers are still confused about the steps from shopping to payment. This is due to the lack of information obtained so the company introduces this innovation through salespeople. The purpose of this activity is to find out the use of technology to facilitate customer access to purchases and payments at Charles & Keith. The method used is ABCD (Asset Based Community Development) with several stages such as preparation stages, implementation stages and monitoring and evaluation stages. The results obtained from this activity show that the company has taken advantage of technological developments that provide a choice of shopping methods via websites and chat shops as well as payments using transfers, QRIS, credit cards, virtual accounts, and others. Customers also received this innovation positively, as monthly results show about the increase in the number of chat shop users.